Ceramics of the Indigenous Cultures of South America : Studies of Production and Exchange through Compositional Analysis - Vaughn, Kevin J.; Neff, Hector; Glascock, Michael (Book collections on Project MUSE., 2019)
This cohesive edited volume showcases data collected from more than seven thousand ceramic artifacts including pottery, figurines, clay pipes, and other objects from sites across South America.